2014
DOI: 10.1039/c3an02371k
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform infrared spectroscopy to quantify collagen and elastin in an in vitro model of extracellular matrix degradation in aorta

Abstract: Extracellular matrix (ECM) is a key component and regulator of many biological tissues including aorta. Several aortic pathologies are associated with significant changes in the composition of the matrix, especially in the content, quality and type of aortic structural proteins, collagen and elastin. The purpose of this study was to develop an infrared spectroscopic methodology that is comparable to biochemical assays to quantify collagen and elastin in aorta. Enzymatically degraded porcine aorta samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 56 publications
(104 reference statements)
4
30
0
Order By: Relevance
“…The same procedure was repeated for a spectroscopic band centered at 1338 cm −1 to map structural proteins, i.e, collagen and elastin and reported as SPR (structural proteins). This band has been observed in the spectra of both collagen and elastin and confirmed with published spectra for these molecules (Cheheltani et al, 2014; Wetzel et al, 2005).…”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…The same procedure was repeated for a spectroscopic band centered at 1338 cm −1 to map structural proteins, i.e, collagen and elastin and reported as SPR (structural proteins). This band has been observed in the spectra of both collagen and elastin and confirmed with published spectra for these molecules (Cheheltani et al, 2014; Wetzel et al, 2005).…”
Section: Methodssupporting
confidence: 86%
“…These include monitoring arterial remodeling after injury (Herman et al, 2009), identification and characterization of vulnerable plaques using characteristic absorption bands of lipids and total protein (Colley et al, 2004; Kazarian and Chan, 2006; Palombo et al 2009), differentiation of normal and aneurysmal human aortas on biopsies of human ascending aortas (Bonnier et al, 2006 and 2008; Rubin et al, 2008), and quantification of collagen and elastin in aortic degradation (Cheheltani et al , 2014). The results of this study showed that the transmural variations of structural proteins and total protein, as measured by FT-IRIS, are consistent with microstructural parameters, and two distinct regions of inner half and outer half could be identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H&E staining confirmed the removal of the DNA content from the two tissue types after decellularization, and the Picrosirius red staining confirmed that the collagenous structure of the ECM was maintained during decellularization (Figure b). The FTIR results for the two ECMs showed peaks in the areas associated with structural proteins such as collagen and elastin, suggesting that the decellularizing process maintained the protein's integrity (Cheheltani, McGoverin, Rao, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Destructive tissue damage characterization methods are suitable only for ex-vivo tissue testing and include histology (with chemical or cryogenic tissue fixation) [8], optical (light) microscopy [9], scanning electron microscopy (SEM) [10][11], and environmental SEM [12][13]. Non-destructive methods are more suited for in vivo tissue testing and include techniques such as optical coherence tomography (OCT) [14][15], ultrasound [16], white light interferometry [17], Raman spectroscopy [18][19], and infrared (IR) spectroscopy [20][21][22]. Of these approaches the most promising for further exploration are the methods based on Raman and IR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%